PEBP1 suppresses HIV transcription and induces latency by inactivating MAPK/NF‐κB signaling. (14th September 2020) - Yang, Xinyi; Wang, Yanan; Lu, Panpan; Shen, Yinzhong; Zhao, Xiaying; Zhu, Yuqi; Jiang, Zhengtao; Yang, He; Pan, Hanyu; Zhao, Lin; Zhong, Yangcheng; Wang, Jing; et al.
Abstract: The latent HIV‐1 reservoir is a major barrier to viral eradication. However, our understanding of how HIV‐1 establishes latency is incomplete. Here, by performing a genome‐wide CRISPR‐Cas9 knockout library screen, we identify phosphatidylethanolamine‐binding protein 1 (PEBP1), also known as Raf kinase inhibitor protein (RKIP), as a novel gene inducing HIV latency. Depletion of PEBP1 leads to the reactivation of HIV‐1 in multiple models of latency. Mechanistically, PEBP1 de‐phosphorylates Raf1/ERK/IκB and IKK/IκB signaling pathways to sequestrate NF‐κB in the cytoplasm, which transcriptionally inactivates HIV‐1 to induce latency. Importantly, the induction of PEBP1 expression by the green tea compound epigallocatechin‐3‐gallate (EGCG) prevents latency reversal by inhibiting nuclear translocation of NF‐κB, thereby suppressing HIV‐1 transcription in primary CD4 + T cells isolated from patients receiving antiretroviral therapy (ART). These results suggest a critical role for PEBP1 in the regulation of upstream NF‐κB signaling pathways governing HIV transcription. Targeting of this pathway could be an option to control HIV reservoirs in patients in the future. Synopsis: The latent HIV‐1 reservoir prevents efficient viral eradication. The phosphatase PEBP1 plays a critical role in the regulation of NF‐κB‐dependent pathways governing HIV‐1 transcription, and its targeting could control HIV reservoirs in patients. Depletion of PEBP1 leads to the reactivation of HIV‐1 in multiple HIV latency models. EGCG induces PEBP1 protein expression and prevents latency reversal in patients receiving antiretroviral therapy. PEBP1 is induced by IFN signaling during HIV‐1 infection and promotes HIV latency in primary CD4 + T cells. Abstract : The latent HIV‐1 reservoir prevents efficient viral eradication. The phosphatase PEBP1 plays a critical role in the regulation of NF‐κB‐dependent pathways governing HIV‐1 transcription, and its targeting could control HIV reservoirs in patients.